Relationship between soil - water characteristic curve and permeability of soil - Hoach, Tuan Kiet. (2012)
Soil – water characteristic curve is an important property that controls behavior of soil such as permeability. A theoretical model for predicting soil – water characteristic curve during drying and wetting processes is developed and verified with experimental data. Two equations for best fitting unimodal and bimodal soil – water characteristic curves are proposed, each parameter of the equations has a physical meaning related to the soil – water characteristic curve. Two hysteresis indices are introduced to predict the change in the soil – water characteristic curve during wetting process. Another two equations are proposed to predict unimodal and bimodal permeability from the knowledge of the soil – water characteristic curve. Results showed that the proposed equations provide good fit for different types of soil with unimodal and bimodal characteristics.